Mediatization of conflict in the social media era: a case study of Sino-Indian border crisis in 2017 - Zhang, Shixin Ivy (Sage, 2019)
Inspired by the concepts of Arrested War and actor–network theory, this study has traced and analyzed four main actors in the wars and conflicts in the social media age: social media platform, the mainstream news organizations, online users, and social media content. These four human and nonhuman actors associate, interact, and negotiate with each other in the social media network surrounding specific issues. Based on the case study of Sino-Indian border crisis in 2017, the central argument is that social media is playing an enabling role in contemporary wars and conflicts. Both professional media outlets and web users employ the functionalities of social media platforms to set, counter-set, or expand the public agenda. Social media platform embodies a web of technological and human complexities with different actors, factors, interests, and relations. These actor-networks and the macro social-political context are influential in the mediatization of conflict in the social media era.